Abraham Swain deposition - Swain, Abraham
Deposition of Swain regarding his United States citizenship.
Master of the brig Industry, sailing out of Baltimore, Md.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Industry (Brig : 1799); Citizenship -- United States; Baltimore (Md.) -- Commerce; Ship captains